The Factors Associated with Lack of Access to Health Facilities among Persons of Concern (PoC) during the COVID-19 Pandemic in Nigeria - Sri Nurcahyati; Mohamad Sadli; Abbani, Abubakar Yakubu; Maretalinia (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2024)
Persons of Concern (PoC) are people displaced because of natural disasters or conflictsand violence, and they include refugees, asylum seekers, internally displaced persons(IDPs), and returnees. Nigeria is one of the major destinations of PoC in Africa. PoCshould have the same rights in any sector, including health access in their destination.However, during the COVID-19 pandemic, about 19% of households faced a lack ofaccess to health facilities in Nigeria. This study examined the factors related to the lackof access to health facilities among PoCs in Nigeria during the COVID-19 pandemicin 2020. Methods: Secondary data from the UNHCR survey, which was conducted inJuly 2020 among 3,222 households categorized as PoC, was used. Univariate, bivariate, and multivariate analyses were used to assess the factors with the aid of STATA 17software. Results: Factors such as state of residence, population status, marital status,and gender of household heads were found to have a significant correlation with thelack of access to health facilities in Nigeria. Conclusion: The UNHCR, the Nigeriangovernment, and other stakeholders must work together to ensure all PoCs can accesshealth facilities easily, especially during outbreaks of pandemics and other disasters.